2009
DOI: 10.1007/s10384-009-0726-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between blue-on-yellow perimetry and scanning laser polarimetry with variable corneal compensation measurements in primary open-angle glaucoma

Abstract: The presence of significant correlations between some B/YP indices and the GDx VCC parameters in glaucoma patients suggests that the two tests can detect similar areas and amounts of glaucomatous damage. These findings raise the possibility that both techniques can be used in clinical examinations to yield convergent data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Those who were less than 18 years old were also excluded. POAG was diagnosed according to the presence of typical glaucomatous abnormal optic nerve changes (localized optic disc notching, thinning or vertical cup-to-disc ratio asymmetry of > 0.2 between eyes, or localized wedge-shaped retinal nerve fiber layer defect) associated with matching glaucomatous visual field defects with standard automated perimetry (SAP), untreated IOP >21 mmHg with Goldmann applanation tonometer (GAT) in at least one eye, open angle on gonioscopy and no clinically apparent secondary cause for their glaucoma [ 16 ]. OHT was defined as having normal optic nerve head and retinal nerve fiber layer, normal visual field with SAP, untreated IOP >21 mmHg with GAT in at least one eye, open angle on gonioscopy and no clinically apparent secondary cause for high IOP [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Those who were less than 18 years old were also excluded. POAG was diagnosed according to the presence of typical glaucomatous abnormal optic nerve changes (localized optic disc notching, thinning or vertical cup-to-disc ratio asymmetry of > 0.2 between eyes, or localized wedge-shaped retinal nerve fiber layer defect) associated with matching glaucomatous visual field defects with standard automated perimetry (SAP), untreated IOP >21 mmHg with Goldmann applanation tonometer (GAT) in at least one eye, open angle on gonioscopy and no clinically apparent secondary cause for their glaucoma [ 16 ]. OHT was defined as having normal optic nerve head and retinal nerve fiber layer, normal visual field with SAP, untreated IOP >21 mmHg with GAT in at least one eye, open angle on gonioscopy and no clinically apparent secondary cause for high IOP [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Standard argon laser treatments (ALT and SLT) increased the aqueous outflow through the trabecular meshwork causing coagulative and structural damage with an increased inflammatory response and pigment dispersion frequently causing transient IOP spikes and ocular discomfort [10][11][12][13][14][15][16]. MLT has been recorded to stimulate a biological response without causing any macroscopic or microscopic changes in the trabecular meshwork, thereby inducing less inflammation and reducing tissue damage [24,25]; this was also confirmed by a histologic analysis performed on human corneoscleral rim tissue from cadaver eyes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, several studies confirmed the positive effects in controlling IOP and favored its diffusion. However, despite proving effective in controlling IOP, normal ocular tissue function has been found to be altered by thermal damage to the trabecular meshwork and its application was limited by several complications resulting from its use, including pressure spikes higher than 10 mmHg in 12% of patients; late spikes, especially in pseudo-exfoliative glaucoma; peripheral anterior synechiae in 15-20% of cases; and damage to the corneal endothelium [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Therefore, early POAG diagnosis has been one of the many clinical problems associated with glaucoma. Increasing numbers of studies have revealed that optic disc morphological changes and visual field defects are important indicators of glaucoma diagnosis, 6,7 as well as a conditional assessment tool. The use of advanced equipment makes a detailed assessment of optic disc morphological changes and visual field defects possible.…”
Section: Introductionmentioning
confidence: 99%